Standards Evaluate The Performance of Emergency Departments In Iraqi Hospitals / Case Study - حمود, سعد علي; عاشور, عقيل مسلم (Journal of Economics and Administrative Sciences, 2014)
This study aims to evaluate the performance of emergency departments according to international standards through studying the performance in some of Iraqi public hospitals, where the evaluation performance is considered one of the important topics that take a great deal of officials' attention, especially decision makers in health organizations.      The researcher has derived the research idea from the importance of work in emergency department in hospitals and to what it provides of medical services and quick and immediate nursing care that help in patients' lifesaving, and it is the mirror that reflects the real image for the hospital and the main window for the medical services that are provided in those hospitals through measuring the important aspects that the performance constitutes, identifying its significance for the purposes of measuring and testing, and then contribution in constructing an evaluation system that can be utilized in developing emergency departments in Iraqi public hospitals.     Based on reviewing the relevant literature, the researcher determined a set of hypotheses, and in an attempt to test these hypotheses, the descriptive analytical method is used, where an international checklist is constructed to evaluate the performance of emergency departments in the studied Iraqi public hospitals that included (13) criteria that are divided into (360) questions. The study is conducted in the emergency departments in four public hospitals in Baghdad city that are: Imam Ali Public Hospital, Baghdad Teaching Hospital, Al-Karkh Public Hospital, and Al-Kadhimiyah Teaching Hospital. Besides the checklist on the study, three other instruments are used in the study that are medical records, real observation,  and personal interview. Several statistical measures are used for data management like arithmetic mean, standard deviation, percentage, ANOVA, Z-test, T-test for one sample, F-test for measuring the associations, and congruency tables.     Based on measuring and determining the study variables, and testing association and the effect and differences among these variables, the researcher has found some important conclusions; of these are the shortage in specialist physicians, permanent physicians, rotator physicians, inadequacy of emergency specialist, and nursing staff, and that the numbers of currently available medical and nursing staffs are not appropriate to the numbers of patients and clients who visit emergency departments in the studied hospitals, besides the lack of the materials necessary in emergency departments as a whole, for their modernity and design, the furniture and their correspondence to international specifications, lack of the medical appliances and equipment where they are not qualified according to the international specification used in measurement, besides unavailability of hospital wards and beds in the studied Emergency department.